Regarding Blinded Visibility (KULT_online, 2021)
The monograph Haunting without Ghosts, written by Juliana Martínez, conceptualizes and exemplifies the narrative form and aesthetics of ‘spectral realism’ in the Colombian arts. The book traverses literary, cinematic and artistic works from the last two decades, presenting the formal tools for expressing narratives of an armed conflict of disclaimed loss and truncated mourning. In short, it analyzes works that do not take ghosts literally but as a perceptual form of expression.